OPERATION OF DRILLED MICROPILES WITH ENLARGED BASE - Hnatiuk О.; Kret В. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
Significant discrepancies have been identified in studies of drilled piles with enlargements, particularly regarding the differences between calculated and experimental values of bearing capacity. This indicates an opportunity to enhance existing methodologies. Ukrainian researchers have made notable contributions to this field by examining the impact of the number and arrangement of enlargements, as well as various soil types, on pile performance. They have developed new methods for calculating bearing capacity, refined calculation coefficients, and validated their reliability through field tests. Considerable focus has also been directed towards concrete-filled steel tube micropiles, which demonstrate superior performance in weak soil conditions and provide advantages such as ease of use and minimal disruption to existing structures. Piles with an enlarged base exhibit higher bearing capacity and reduced settlement compared to friction piles. Numerical modeling utilizing PLAXIS 3D and ANSYS WORKBENCH has confirmed the effectiveness of these structures and enabled accurate simulations of their behavior. It was determined that the depth, number, and diameter of enlargements significantly influence strength and deformation characteristics. Technical and economic assessments have shown that the use of drilled micropiles with enlargements is feasible in densely built-up areas, leading to reductions in demolition and earthwork costs. Overall, this research underscores the importance of further enhancing calculation models and adopting innovative structural solutions in pile foundations.